A Colony of Euglandina Rosea at Beaufort, North Carolina - Douglas A. Wolfe; Jeraldine H. Brooks (Hello World!, 1968)
The range of the carnivorous land snail Euglandina rosea (Ferussac) was reported by Pilsbry (1946) to extend from the vicinity of Yemassee, South Carolina, along the coastal plain south and west into Louisiana, including all of Florida. Burch (1962) gave the range as South Carolina, Florida, Alabama, Mississippi and Louisiana. The northernmost record is Charleston, South Carolina (Mazyck 1913). The present report concerns a colony of living Euglandina rosea at Beaufort, North Carolina, some 260 miles north and east of Mazyck's Charleston record.